Traumatic brain injury extending to the striatum alters autonomic thermoregulation and hypothalamic monoamines in recovering rats - Verduzco-Mendoza, Antonio; Mota-Rojas, Daniel; Olmos Hernández, Silvia Adriana; Gálvez-Rosas, Arturo; Aguirre-Pérez, Alexander; Cortes-Altamirano, José Luis; Alfaro-Rodríguez, Alfonso; Parra-Cid, Carmen; Avila-Luna, Alberto; Bueno-Nava, Antonio (Frontiers in Neuroscience, 2023)
The brain cortex is the structure that is typically injured in traumatic brain injury (TBI) and is anatomically connected with other brain regions, including the striatum and hypothalamus, which are associated in part with motor function and the regulation of body temperature, respectively. We investigated whether a TBI extending to the striatum could affect peripheral and core temperatures as an indicator of autonomic thermoregulatory function. Moreover, it is unknown whether thermal modulation is accompanied by hypothalamic and cortical monoamine changes in rats with motor function recovery. The animals were allocated into three groups: the sham group (sham), a TBI group with a cortical contusion alone (TBI alone), and a TBI group with an injury extending to the dorsal striatum (TBI+striatal injury). Body temperature and motor deficits were evaluated for 20 days post-injury. On the 3rd and 20th days, rats were euthanized to measure the serotonin (5-HT), noradrenaline (NA), and dopamine (DA) levels using high-performance liquid chromatography (HPLC). We observed that TBI with an injury extending to the dorsal striatum increased core and peripheral temperatures. These changes were accompanied by a sustained motor deficit lasting for 14 days. Furthermore, there were notable increases in NA and 5-HT levels in the brain cortex and hypothalamus both 3 and 20 days after injury. In contrast, rats with TBI alone showed no changes in peripheral temperatures and achieved motor function recovery by the 7th day post-injury. In conclusion, our results suggest that TBI with an injury extending to the dorsal striatum elevates both core and peripheral temperatures, causing a delay in functional recovery and increasing hypothalamic monoamine levels. The aftereffects can be attributed to the injury site and changes to the autonomic thermoregulatory functions.